انتشارُ الحَؤُولِ المِعَوِيِّ المَعِدِيِّ من خلالِ التنظيرِ الهضميِّ العُلويِّ والدِّراسةِ النَّسيجيَّةِ وترافُقِ المُلتويةِ البوَّابيَّةِ معهُ في المشافي الجامعيَّةِ بجامعةِ تِشرين - حماد, اسماعيل; دغمان, دعد; داود, علي; سعيد, جعفر (Latakia University Journal -Medical Sciences Series, 2018)
يُعرَف الحَؤولَ المِعويَّ المعديَّ gastric intestinal metaplasia (GIM) كعاملِ خطورةٍ هامٍّ لسرطان المعدة الَّذي لا يزالُ رابعَ أكثرِ أنواعِ السَّرطاناتِ شُيوعاً والسَّببَ الرَّئيسيَّ الثَّانيَ للوفيَّاتِ السَّرطانيةِ في العالم بعد سرطانِ الرِّئة. ذكرت بعضُ الدِّراساتِ السَّريريةِ بأنَّ الحؤول المعوي يتحسَّنُ أو يهجع بعد علاجِ الإنتانِ بالملتوية البوَّابيَّة، وكنتيجةٍ لذلك فإنَّ استئصال الملتوية البوَّابيَّة هو واحدٌ من أكثرِ الأساليبِ الواعدة في منعِ حُدوثِ سرطانِ المعدة. الهدف من البحث استقصاءُ نِسبةِ انتشارِ الحَؤول المعويّ المعديّ و أنماطِه subtypes، و مُعدَّل ترافُقِ الإنتان بالمُلتويةِ البوَّابيَّة HP معه. حيث أُخِذت خزعات معدية من 200 مريضاً في مشافي جامعة تشرين بمحافظة اللاذقية في الفترة بين شهر كانون الثاني 2016 م وشهر نيسان 2017 م. تمَّ تلوينُ الخزعات بالهيماتوكسيلين إيوزين لتحديد نمط الحَؤُول المعوي, وتمَّ تحرِّي المُلتوية البوَّابيَّة بملوِّن غيمزا. بلغت نسبة انتشار الحؤول المعوي المعدي (16%). النمط التَّام كان أعلى انتشاراً من النمط غير التَّام. ترافقت الملتوية البوابية بنسبة (50%) مع الحؤول المعوي المعدي، دون وجود أهمية إحصائية ( P > 0.05). ترافق التهاب المعدة المزمن بنسبة (100%) مع الحؤول المعوي المعدي ( P Value = 0.02). الحؤول المعوي المعدي كان أعلى انتشاراً عند كبار السِّن. أظهرت دراستنا أنَّ الحؤول المعوي المعدي موجود بشكل ملحوظ في المرضى الخاضعين للتنظير الهضمي العلوي والخزعات المعدية في منطقتنا. يُعتبر التهاب المعدة المزمن من أهم أسباب تطور الحؤول المعوي المعدي. gastric intestinal metaplasia (GIM) is considered to be a precursor of gastric cancer which is still the fourth most common cancer and second leading cause of cancer related death worldwide after lung cancer. There is also a relationship between gastric intestinal metaplasia and H.pylory which is one of the most important factors predisposing it . As a result, H. pylori eradication is one of the most promising approaches in gastric cancer prevention. The aim of the study was investigated the prevalence of GIM and its subtypes, and the prevalence of H. pylori infection in GIM. the study was conducted on 200 patients who were undergoing esophagogastroduodenoscopy (EGD) with biopsy between January 2016 and April 2017, in the university hospitals of Tishreen university. Specimens were stained with hematoxylin and eosin to determine the pattern of intestinal metaplasia. And Helicobacter pylori was investigated by Giemsa staining. The prevalence of GIM was 16%. The prevalence of complete IM was higher than incomplete IM. The prevalence of H. pylori infection was 50% in GIM, without presence of statistical importance ) P > 0.05). The prevalence of chronic gastritis was 100% in GIM (P Value = 0.02). Gastric intestinal metaplasia was more prevalent in older patients. GIM is a common finding in patients undergoing EGD with biopsy in our region. Chronic gastritis is considered as the most important reason for the development of GIM.